IAEA Atlas of Cardiac PET/CT A Case-Study Approach - Di Carli, Marcelo F.; Dondi, Maurizio; Giubbini, Raffaele; Paez, Diana (Springer Nature, 2022)
This open access book presents a wide portfolio of examples of positron emission tomography coupled with computer tomography (PET/CT) studies in various cardiac conditions in order to provide a rationale for the implementation of this technology in an array of clinical conditions. Cardiovascular diseases are a major contributor to premature morbidity and mortality worldwide. Low- and middle-income countries (LMICs) are particularly affected by cardiovascular diseases (CVDs), with more than 75% of all CVDs deaths occurring in these countries. For this reason, target 3.4 of the United Nations (UN) Sustainable Development Goals (SDGs) agenda aims at a 30% reduction in premature mortality due to non-communicable diseases (NCDs), which include CVDs, by 2030. Among CVDs, ischemic heart disease (IHD) plays an important role and, according to the Institute for Health Metrics and Evaluation (IHME), it was responsible for 15.96% of global deaths in 2017. Between 2000 and 2017, the number of IHD deaths worldwide increased by 0.26% per year. Several imaging tools help to non-invasively diagnose, stratify risk and guide management in cardiac disease. They include nuclear cardiology techniques, using either SPECT (single photon emission computed tomography) or PET/CT. While myocardial imaging with SPECT has been fully embraced by the cardiology community and is widely available worldwide, PET/CT introduction has been slower, due not only to its higher costs, but also to the limited availability of PET/VCT scanners, mostly utilized for oncological applications. This book is an invaluable tool for nuclear medicine physicians, cardiologists and radiologists.